Ibn Taymiyya's Sufism Education Model in Strengthening the Religious Moderation of Indonesian Society - Muvid, Muhamad Basyrul (AL-TAHRIR, 2024)
Radical ideology is a big problem for the Indonesian people in maintaining integrity and unity. The concept of religious moderation is a strength in maintaining the diversity and integrity of this nation. The science of Sufism is an alternative to developing moderate character with a humanist model of Sufism through Ibn Taymiyya's thoughts. This research aims to find Ibn Taymiyya's model of Sufism education to strengthen religious moderation in society. The research method used was a character biographical study, namely conducting a study of thoughts, life stories, and works produced. Data analysis used induction and interpretation techniques supported by relevant library sources so that the data presentation was more focused and valid. The study results concluded that Ibn Taymiyya's Sufism education model upholds the concepts of tawazun, tasamuh, ta'dil, tawasuth, which can encourage the formation of attitudes and moderate character. The moderate character positively impacts the maturation of social attitudes, which are beneficial for forming a complete, tolerant, and tolerant life. This attitude becomes a reinforcement in maintaining state sovereignty and togetherness between individuals. Ibn Taymiyya's model of Sufism education in practice and concept can form a moderate attitude so that religious understanding can be understood wisely, far from blind fanaticism and exclusive attitudes that can form gaps between individuals. The limitations of this research only extend to the analysis of Ibn Taymiyya's Sufism education model, which is relevant to the concept of religious moderation. The development direction for further research can be focused on Ibn Taymiyah's multicultural-based model of Sufism education in response to the era of artificial intelligence (AI).